THE SOUTHERMOST RECORD OF THE GENUS MYTILOPSIS: A NEW SPECIES OF DREISSENIDAE (MOLLUSCA, BIVALVIA) FOUND IN THE PARANÁ FORMATION (UPPER MIOCENE; ARGENTINA) (Ameghiniana, 2025)
A new species of bivalve of the Family Dreissenidae is established, based on material found in the Paraná Formation (Upper Miocene)exposed in the province of Entre Ríos, Argentina. Mytilopsis parodizi sp. nov. is the first member of the family to be described and illustrated from southern South America and represents the southernmost known record for the genus. The new species was found in a mixed fossil deposit, in association with various taxa characteristic of marine, brackish, freshwater, and terrestrial environments, all within the same stratigraphic level exposed at the locality known as ‘La Juanita’ (Department of Diamante). The presence of M. parodizi sp. nov. at this latitude (ca. 31° S) confirms a more widespread southern distribution of the genus compared to the current one, supporting the hypothesis of an arrival to the region through bodies of brackish water, along the Atlantic margin of South America, or perhaps profiting from occasional connections among shallow inland basins, and possibly also from passive dispersal aided by wandering waterfowl.